Biegeumformen mit Elastomerwerkzeugen : Modellierung, Prozessauslegung und Abgrenzung des Verfahrens am Beispiel des Rohrbiegens - Nock, Marco (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2005)
Decreasing product cycle times as well as more and more individual prospects on products make modern manufacturing technologies necessary which enable an efficient and flexible production of parts. A group of technologies fulfilling these demands is forming using an elastomere tool. This work shows, exemplarily for bending of tubes using an elastomere pad, strategies for a virtual process design as well as for an online process control. For a virtual process design by using finite element simulation, suitable methods for the characterisation, for the choice of a material model and the modelling of the process are presented. Within the scope of a process control a foil measurement system has been realised. By using this system contact stresses between elastomere tool and workpiece can be detected and monitored. The potential of the technology of bending using an elastomere tool is shown on the basis of the resulting properties of the produced part